Ebstein anomaly associated with cri du chat (cat's cry) syndrome and 20q duplication (2020)
Ebstein anomaly is a congenital heart defect with a low prevalence and high mortality in the early stages of life. In medical literature, there is no reported association between Ebstein anomaly and cri du chat syndrome. Here, we report the case of a full-term newborn with a low weight for his age and who had a prenatal diagnosis of Ebstein anomaly and a postnatal diagnosis of cri du chat syndrome and 20q duplication detected on array CGH. The patient required medical treatment with inotropic support, high-frequency ventilation and nitric oxide, with an adequate response. Surgical intervention was not needed.